Asymmetric synthesis of aryloxypropanolamines via OsO4-catalyzed asymmetric dihydroxylation - Sayyed, I. A.; Thakur, V. V.; Nikalje, M. D.; Dewkar, Gajanan; Kotkar, S. P.; Sudalai, A. (Tetrahedron, 2005)
A simple and effective procedure for the enantioselective synthesis of several beta-adrenergic blocking agents incorporating the first asymmetric synthesis of celiprolol, is described. The key steps are (i) sharpless asymmetric dihydroxylation of aryl allyl ethers to introduce chirality into the molecules and (ii) conversion of cyclic sulfates into the corresponding epoxides using a three-step procedure. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: antihypertensive; asymmetric dihydroxylation; cyclic sulfates; epoxides

Influence of starting precursors and synthesis methods on the physiochemical properties of zirconia - Gaydhankar, T. R.; Jha, Ratnesh Kumar; Nikalje, M. D.; Waghmare, K. J. (Materials Research Bulletin, 2014)
Under identical and judiciously pre-optimized synthesis conditions, the influence of different combinations of zirconium sources and/or post treatment conditions on structural properties, thermal stability, phase composition and morphology of zirconia has been investigated. High surface area tetragonal zirconia could be synthesized in a cost-effective manner from 1 M solution of zirconium oxynitrate at pH 11 using aqueous ammonia solution as a precipitant when calcined at 400 degrees C for 3 h. Irrespective of the preparation method, pH and starting precursor, zirconia samples prepared without digestion contained dominant monoclinic phase with some traces of tetragonal phase when calcined at 700 degrees C. Even though there is linear decrease in surface area with increase in the crystallite size for each sample as a function of calcination temperature, no co-relation between the surface area and crystallite size could be achieved. SEM images show agglomerated and irregular shape particles between 10 to 20 mu m. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Oxides; Sol-gel chemistry; Thermogravimetric analysis (TGA)

Enantioselective reduction of ketones and synthesis of 2-methyl-2,3-dihydro-1-benzofuran catalyzed by chiral spiroborate ester - Patil, H. S.; Nikalje, M. D.; Chopade, A. U.; Chopade, M. U. (Russian Journal of Organic Chemistry, 2021)
Asymmetric reduction of homobenzylic ketones was achieved through the use of chiral spiroborate ester catalyst. The catalyst is applicable for both analytical and industrial purposes since it is not sensitive to air and moisture. A rapid synthetic route has been developed for the preparation of (S)-2-methyl-2,3-dihydro-1-benzofuran via enantioselective reduction of homobenzylic ketone in the presence of a chiral spiroborate catalyst as the key step.
Keywords: 2-methyl-2; 3-dihydro-1-benzofuran; asymmetric reduction; spiroborate ester